Zooming in with QSPR on Friedel-Crafts acylation reactions over modified BEA zeolites - Aleixo, Odrigo (2020)
The catalytic behaviour of hierarchical BEA zeolites with Si/Al ratio of 12.5 and 32 was studied in Friedel-Crafts acylation reactions using furan, anisole and pyrrole as substrates and acetic anhydride as acylating agent. Hierarchical BEA samples were submitted to alkaline and alkaline + acid treatments. Kinetic modelling using nonlinear regressions applied to a simplified Langmuir-Hinshelwood equation showed that the Si/Al ratio of the parent materials strongly influenced the catalytic behaviour. Catalytic results were correlated with physicochemical properties using a Quantitative Structure-Property Relationship (QSPR) methodology. This approach provided detailed information about the role of key properties on the catalytic behaviour, and pointed out which properties should be modified through direct synthesis and/or post-synthesis treatments to obtain materials with optimized catalytic performance.